HERBS USED AS ANALGESIC BY DAYAK TRIBE IN NORTH KALIMANTAN INDONESIA - Irma Novrianti; Faizal Mustamin; Suharjono Suharjono (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2020)
Traditional medicines produced from medicinal plants have played an important role in disease treatment in Dayak Tribe, North Kalimantan. Northern Kalimantan belongs to a remote area where health facilities like healthcare center (puskesmas pusat kesehatan masyarakat) and hospital are not easily accessible. This research aims to investigate herbs used by Dayak tribe in North Kalimantan for treating pain. It is a descriptive research applying two research methods i.e. observation and interview. We directly observed the research object and proposed questions to respondents that were traditional healers from each village. The research was conducted in nine villages within three regencies in North Kalimantan. Meanwhile, 38 herbs collected in this research were from 26 families and 34 species. Four species were still locally named. The highest proportion of the herb family used was Asteraceae. The most frequently used part of the herb for medicine was the leaf (60.53%). The main serving methods were by boiling the herb and drinking it (63.15%). Bone pain and stomachache were two main illnesses mostly treated by local herb therapy involving 11 herbs. In conclusion, Dayak tribe in North Kalimantan still used herbs to treat their pain.